Correlation between particle spectra and elliptic flow - Tribhuban Parida; Rupam Samanta; Jean-Yves Ollitrault (Physics Letters B, 2025)
We introduce a new observable to probe the collective nature of the radial expansion of the quark-gluon plasma. This observable, dubbed v02(pT), represents the correlation of the spectrum with elliptic flow, in the same way as the recently measured v0(pT) represents the correlation of the spectrum with the transverse momentum per particle. The advantage of v02(pT) over v0(pT) is that it is measured using a three-particle cumulant, as opposed to a pair correlation, which significantly reduces the sensitivity to nonflow effects. We predict non-trivial differences between v02(pT) and v0(pT) in semi-central Pb+Pb collisions at the Large Hadron Collider (LHC) on the basis of hydrodynamic simulations. A hint of these differences can be seen in the modification of pT spectra observed by ALICE in event-shape-engineered events.